International Trade in Perspective Investment Law in Indonesia - Widjaja, Andi Arif; Widiarty, Wiwik Sri (International Journal of Artificial Intelligence Research, 2022)
Globalization has significantly changed international trade law and investment in countries like Indonesia. To improve people's welfare through international trade and foreign investment, because the more significant the output, the greater the foreign exchange that comes in, so that it becomes a source of income for the state treasury. To accelerate the national economy's growth and realize Indonesia's political and economic sovereignty, investment must be increased to transform economic potential into economic power. This study employs a normative juridical research approach, namely a procedure to identify the rule of law, legal principles, and legal doctrines about foreign commerce and investment in Indonesia. The problem of this research is 1). How is international trade regulation from the perspective of investment law in Indonesia? 2). What forms of international trade and investment are based on Law Number 25 of 2007 concerning Investment? This research resulted in the following conclusions: Regulations should be in international trade and investment, and regulations on taxes and agreements set forth by investment companies. The Forms of International Trade are divided into 2, namely bilateral trade and multilateral trade.